Persepsi Pendamping Terhadap Pelaksanaan Program Upsus Pajale Di Daerah Istimewa Yogyakarta - Urfan Faridhavin; Roso Witjaksono; Harsoyo Harsoyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2016)
In an effort to realize food security, the Ministry of Agriculture made a policy of agricultural development by preparing food self-sufficiency program embodied with Special Effort of Increasing Productivity of Rice, Corn and Soy (UPSUS PAJALE). This escort and assistance is conducted by Agricultural Extension (PNS and THL), BABINSA (Bintara Pembina Desa) and students. This research aim to know 1) the implementation of UPSUS PAJALE program in Yogyakarta Special District; 2) the perception rate of program adviser to implementation of UPSUS PAJALE program; and 3) the factors which affect to the perception of program adviser. The research used descriptive method. The sampling of location was chosen purposively, while the sampling of program adviser was taken by simple random sampling and total sample is 40 respondents. The data were analyzed with proportion test and multiple linier regression. The research results showed that the rate of program adviser perception to implementation UPSUS PAJALE program was in good category. Knowledge of program adviser positively affect to the perception. Factors that did not significantly influence to perception of program adviser were experience, motivation to work in agriculture, interaction with farmers, interaction with agricultural extention worker, and interaction with BABINSA (TNI).